'So maybe I'm not such an imposter': becoming an academic after a life as a teacher-practitioner. Issue 1 (2nd January 2022) - Hardy, Alison; Murray, Rowena; Thow, Morag; Smith, Michelle
ABSTRACT: The practitioner-academic transition can be a challenge. There are often tensions and difficulties involved in identity change, key aspects of which are writing, publishing, and maintaining the writing habit. In order to support this transition, the writing meeting framework, originally designed to support academic writers in changing and maintaining their writing behaviours, was trialled and evaluated with early career academics who were previously teachers in schools or colleges. We aimed to investigate whether the framework could support former practitioners in changing and maintaining their writing behaviours. Six participants met regularly in pairs to set writing goals and check on progress. Participants were interviewed, and transcripts analysed using self-determination theory to understand what happened in the meetings and whether the framework helped participants to write, keep writing and feel part of a network. Our analysis explored the extent to which it met three psychological needs (competence, relatedness and autonomy). We found evidence that it did, but with varying degrees. We also found that relationships between pairs were important, and that a beneficial writing meeting required a mutualistic relationship. Findings suggest that the framework can, in certain conditions, help former practitioners to maintain change in their writing behaviour so as to be able to perform an aspect of academic work that can be particularly challenging for them during the practitioner-academic transition.